Biocompatibility versus peritoneal mesothelial cells of polypropylene prostheses for hernia repair, coated with a thin silica/silver layer. Issue 6 (29th April 2016) - Muzio, Giuliana; Perero, Sergio; Miola, Marta; Oraldi, Manuela; Ferraris, Sara; Vernè, Enrica; Festa, Federico; Canuto, Rosa Angela; Festa, Valentino; Ferraris, Monica
Abstract: Hernias are generally repaired using synthetic prostheses. Infection may already be present or develop during implantation. Based on the increasing resistance to antibiotics, and the well‐known antimicrobial properties of silver (Ag), the possibility of coating hernia prostheses with a nanostructured layer containing Ag was explored. Prostheses (Clear Mesh Composite [CMC]) made up of two polypropylene layers (macroporous light mesh and thin transparent film) were tested with human mesothelial cells from omentum biopsies. Mesotheliocytes modulate abdominal wall healing producing cytokines, growth factors, and adhesion molecules. Evaluating the growth of these cells on CMC or film alone showed that cell numbers on CMC increased over time, and were higher than those on film alone. Vimentin immunostaining confirmed the cells to be mesotheliocytes. Subsequently, the biocompatibility of mesh layer, coated or not with a thin layer of Ag/SiO2 ‐nanoclusters, was analyzed, showing no difference in absence or presence of Ag/SiO2 . Differently, TGF‐β2 production, involved in tissue repair and fibrosis, increased in the presence of Ag/SiO2 . Moreover, Ag/SiO2 ‐coated mesh showed antibacterial properties. In conclusion, the mesh layer coated with Ag/SiO2 afforded cell growth, and showed antibacterial activity. Coating only the mesh layer did not decrease film transparency, and did not favor the formation of adhesions on the visceral side. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1586–1593, 2017.